PENGEMBALIAN POTENSI KERUGIAN KEUANGAN NEGARA DALAM TAHAP PENYELIDIKAN KASUS KORUPSI YANG TERJADI DI LEMBAGA PEMBIAYAAN EKSPOR INDONESIA (LPEI) - Maharani Putri Intan Nurhaliza (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2024)
Abstract: This study aims to determine the chronology of corruption cases and to find out whether the return of potential state financial losses can eliminate the crime in corruption cases that occur in the Indonesian Export Financing Agency (LPEI). This type of research is normative and conducted based on prescriptive nature. This research uses a normative approach with library research techniques. The corruption case that occurred at the Indonesian Export Financing Agency (LPEI) is still continuing in the process of the examination stage of law enforcement and there is a possibility of increasing the number of companies involved in this corruption case, so that the potential for state financial losses that can harm the state economy and hinder national development can increase. Return of assets by companies involved in criminal acts of corruption that occurred at the Indonesian Export Financing Agency (LPEI), before a legally binding verdict, this cannot eliminate the crime, but can be a mitigating reason for the judge's consideration to impose a verdict.